Temperature control of vibrating heat-generating hardware using spray evaporative cooling in the nucleate boiling region. (5th January 2022) - Sarmadian, A; Dunne, J.F.; Thalackottore Jose, J.; Long, C.A.; Pirault, J-P
Highlights: Newly-designed spray evaporative cooling system analysed and experimentally verified. Optimum linear system model successfully obtained by solving Wiener-Hopf equation. Stable temperature control verified for heat-generating vibrating hardware. Negative PID proportional gain is found to ensure most favourable performance. Abstract: A temperature control approach using evaporative spray cooling of vibrating surfaces in the nucleate boiling region is proposed and verified experimentally. This is relevant to temperature control of heat-generating automotive vehicle components. By exploiting an experimentally calibrated dynamic correlation model to represent evaporative spray cooling of a flat test-piece, a PID controller has been adopted with emphasis focused on the choice of gain parameters to ensure both stability of temperature control, and favourable responses in terms of relevant performance measures. Optimum linearisation of the correlation model has been achieved by solving an appropriate Wiener-Hopf equation, mainly to undertake a practical stability assessment of the closed-loop temperature control system. To verify the predicted control system performance, experimental measurements have been obtained from an instrumented, and spray-evaporatively-cooled, flat test-piece exposed to displacement vibration from a shaker. Experimental testing, appropriate to automotive vehicle component applications, includes large-amplitude, low frequency vibration at 12 mm and 1.9 Hz, and low amplitude, high-frequency vibration at 0.02 mm and 400 Hz. To assess the effects of different PID controller gains on the thermal performance of the thermal management system, a coefficient of performance (COP) is used, defined as the ratio of heat power removal to the required pumping power. To achieve a reduction in the settling time, and an increase in the rise time of stable control, a PID controller with a negative proportional gain showed most promising results. A 10.5% increase in COP was achieved in comparison to a PID controller with positive gains. This information is useful for the design and optimization of thermal management systems using evaporative spray cooling.